THE EFFECT OF WORK STRESS AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT SANGIR SOLOK SELATAN NATURAL ENCHANTMENT HOTEL - Jhons Fernos; Roni Putra (Jurnal Bina Bangsa Ekonomika, 2022)
Performance is a form of good work in a straight line during a certain period in completing a task in comparison with various possibilities, such as standard work results, targets or goals, and criteria that have been determined and agreed together. The purpose of this study was to find out the Effect of Work Stress and Job Satisfaction on Employee Performance at Sangir Solok Selatan Natural Enchantment Hotel. This type of research is quantitative. The population of this research is all employees of Pesona Alam Sangir Hotel which amounts to 36 people. Data is processed using multiple linear regressions using questionnaires. The results showed that there was a negative and significant effect of work stress on employee performance with a calculated t value of -3.046 < t table 1.990, and a sig value of 0.005 < 0.05, then it can be concluded that Ha was accepted and Ho was rejected and there was a positive and significant effect of job satisfaction on employee performance with a calculated t value of 5,552 < t table 1,990, and a value of sig 0.000 < 0.05, then it can be concluded that Ha is accepted and Ho is rejected and advised to the company needs to make an innovation so that employees do not easily feel bored in doing work that will later be able to cause prolonged work stress. The way that can be done for example by holding sports activities together, in addition can also be done training conducted outside the work environment, or outbound, in order to increase the cooperation relationship between employees